Perspectives and knowledge levels of university students on chemical and behavioral addictions - Sanal Özcan, Yasemin; Hamzaoğlu, Nurcan; Türk, Burcu (Journal of Dependence, 2020)
Objective: The present study aims to measure the knowledge levels of university students about chemical and behavioral addictions. Method: The sample of the study consists of 422 students. The students who participated in the descriptive study, answered a printed questionnaire consists of 4 part created by the researchers to evaluate their access to various substances, their beliefs about addiction treatments, their opinions about whether or not various substances are harmful to health, whether they are aware of the legal sanctions. Results: Participants’ access to various substances varies between 15-30%. The rate of students who know someone who uses addictive substance is between 10-30%. 14.2% of the participants think that there is no legal sanction/penalty for substance use. In the question on effectiveness of addiction treatment, it has been seen that the respondents answered “cannot be quitted even if medical treatment is taken” in the rates changing from 5.2-15.7%, while respondents that range between 12.1-38.7% answering “can not be quit without treatment”. Conclusion: There are wrong or inconsistent beliefs and knowledge among students about the negative consequences of addiction, legal sanctions on substance use, the efficacy of addiction treatments and the causes of different types of addictions.